ANALYSIS OF THE IMPLEMENTATION OF THE JUST-IN-TIME SYSTEM IN PRODUCTION COST EFFICIENCY AND OPERATIONAL PERFORMANCE OF THE DESMON GARMENT BUSINESS - Muhammad Ilham Sembiring; Waizul Qarni; Atika (Pena Cendekia Insani, 2025)
This study aims to analyze the impact of implementing the Just In Time (JIT) production system on cost efficiency and operational performance at Desmon Garment Business in Medan City. JIT is a production approach that focuses on waste reduction and operational efficiency by producing goods according to actual demand. The research method used a qualitative approach through surveys and document analysis. Data were collected via questionnaires, interviews, and secondary data such as production and cost reports. The findings reveal that JIT implementation reduced total production costs by 6.53% and improved operational performance, including increased output, shortened lead time, and reduced defect rates. JIT also enhanced work coordination and responsiveness to market demand. Therefore, the JIT system is proven to be effective in improving efficiency and competitiveness in small and medium-sized garment enterprises.